Improving Learning Outcomes of Islamic Religious Education Students of State Vocational High School 3 Raha Through Learning the TAI Model (Team Assisted Individualization) - St Aminah (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
As leaders in the class, teachers are always expected to have tricks to design knowledge that can attract students' interest as members of their learning. So it is not surprising that subject teachers must be more creative in compiling teaching materials, determining suitable learning models, and attracting students' attention in-class lessons. This needs to be done because the appropriate teaching materials and methods will affect students' processes and learning outcomes in the classroom. One of the learning models that can be used in teaching Islamic Religious Education is the TAI (Team Assisted Individualization) type cooperative model. This learning model emphasizes students play an active role in learning, both in groups and independently. Classroom Action Research was conducted on students of the Class XI Clothing Boutique Department of Vocational High School Raha for the 2019/2020 academic year with subject matter focused on the procedures for carrying out sermons, tabligh, and da'wah in the community with basic competencies in applying the provisions of sermons, tabligans, and da'wah. In society, according to Islamic law. The results showed that students' learning outcomes in the Boutique Clothing Department Class XI Clothing IV at Vocational High School Raha through the cooperative learning model of TAI (Team Assisted Individualization) type increased. The percentage of students' completeness classically in the pre-cycle is 66.93%, the first cycle is 70.16%, and the second cycle is 79.83%.